2006
DOI: 10.1063/1.2220531
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and band alignments for Ge3N4 dielectrics on Ge

Abstract: Ge 3 N 4 dielectrics were prepared on Ge surface by in situ direct atomic source nitridation. The thermal stability and band alignments for Ge3N4∕Ge interfaces have been studied by using high-resolution x-ray photoemission spectroscopy. The in situ thermal treatment shows that Ge3N4 film has higher temperature thermal stability up to 550°C in vacuum. The conduction- and valence-band offsets at Ge3N4∕Ge interface are quite asymmetrical with the values of 2.22 and 1.11eV, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…To minimize the possible leakage current, the conduction band offset ͑CBO͒ or valence band offset ͑VBO͒ needs to be larger than 1 eV. The band offsets of amorphous Ge 3 N 4 on Ge͑001͒ had been evaluated by Wang et al 5 using XPS, and the corresponding CBO and VBO are about 2.22 and 1.11 eV, respectively. However, the study of band offsets of crystalline Ge 3 N 4 / Ge͑111͒ is still limited, whether theoretically or experimentally.…”
mentioning
confidence: 99%
“…To minimize the possible leakage current, the conduction band offset ͑CBO͒ or valence band offset ͑VBO͒ needs to be larger than 1 eV. The band offsets of amorphous Ge 3 N 4 on Ge͑001͒ had been evaluated by Wang et al 5 using XPS, and the corresponding CBO and VBO are about 2.22 and 1.11 eV, respectively. However, the study of band offsets of crystalline Ge 3 N 4 / Ge͑111͒ is still limited, whether theoretically or experimentally.…”
mentioning
confidence: 99%
“…The valence-band edge of Ge 3 N 4 was determined to be 1.21 AE 0.04 eV. Wang et al [10] reported that the energy difference between the valence-band edge and the Ge3d CL peak of Ge substrate is constant with and without an overlayer. Therefore, the VBO at the Ge 3 N 4 /Ge interface is determined to be…”
mentioning
confidence: 99%
“…The major obstacle has been the sample growth. However, a very recent study reported an in situ Ge 3 N 4 growth on Ge, demonstrating high thermal stability and large band offsets with respect to the Ge system 17 . In this comprehensive work, we present the ab initio structural and electronic properties of all these materials considering their common polymorphs; these are for SiO 2 : α-quartz, α-and β-cristobalite and stishovite phases, for GeO 2 : α-quartz, and rutile phases, for Si 3 N 4 and Ge 3 N 4 : α-and β-phases and for Al 2 O 3 : α-phase.…”
Section: Introductionmentioning
confidence: 99%